2023
DOI: 10.1097/pcc.0000000000003180
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive, Psychosocial, and Quality of Life Outcomes After Multisystem Inflammatory Syndrome in Children Admitted to the PICU*

Abstract: OBJECTIVES: To investigate neurocognitive, psychosocial, and quality of life (QoL) outcomes in children with Multisystem Inflammatory Syndrome in Children (MIS-C) seen 3–6 months after PICU admission. DESIGN: National prospective cohort study March 2020 to November 2021. SETTING: Seven PICUs in the Netherlands. PATIENTS: Children with MIS-C (0–17 yr) admitted to a PICU. INTERVENTIONS: None. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 19 publications
2
25
2
Order By: Relevance
“…Two earlier clinic-based studies directly assessed longer-term neurological outcomes in children after MIS-C. Penner et al found that 6 months after hospitalization, 39% of children had abnormal neurological examination findings, compared with 25% in our study. Our lower rate of neurological abnormalities may reflect fewer neurological sequelae associated with more recent SARS-CoV-2 variants, earlier recognition of MIS-C, relaxation of restrictions, or improvements in MIS-C treatment .…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…Two earlier clinic-based studies directly assessed longer-term neurological outcomes in children after MIS-C. Penner et al found that 6 months after hospitalization, 39% of children had abnormal neurological examination findings, compared with 25% in our study. Our lower rate of neurological abnormalities may reflect fewer neurological sequelae associated with more recent SARS-CoV-2 variants, earlier recognition of MIS-C, relaxation of restrictions, or improvements in MIS-C treatment .…”
Section: Discussioncontrasting
confidence: 53%
“…Our lower rate of neurological abnormalities may reflect fewer neurological sequelae associated with more recent SARS-CoV-2 variants, earlier recognition of MIS-C, relaxation of restrictions, or improvements in MIS-C treatment . A recent Dutch study of children hospitalized in the ICU for MIS-C found normal intelligence but increased emotional problems and lower quality of life than population norms 4 months after hospitalization. We found a similar pattern in MIS-C cases compared with community-based controls more than 6 months after discharge, despite easing pandemic restrictions that may have affected physical activity, mental health care, and education.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Despite these limitations, the study by Otten et al (14) highlights the importance of comprehensive patient follow-up and the unique benefits of incorporating standardized PICU follow-up into routine clinical care. The Dutch Association for Pediatrics has implemented a guideline of care that recommends that every PICU in the Netherlands provide follow-up for patients with unplanned admissions, those who are previously healthy, and those who experience organ failure or receive PICU therapies such as mechanical ventilation or central venous access.…”
mentioning
confidence: 99%